The counselors of Clark Air Base Schools their functions and services - Burt, Beverly J. (s.n.], 1972)
This study looked into the preparation of the guidance counselor, and the functions and services he performs at the Clark Air Base Schools. The closed questionnaire, which was the basic tool used, covered six areas: (1) Functions to the Students; (2) Functions to the Teachers; (3) Functions to the Administration; (4) Functions to the Community; (5) Rescue Services; and (6) Services.